Survival, Morbidities, and Developmental Outcomes among Low Birth Weight Infants with Congenital Heart Defects - Puia-Dumitrescu, Mihai; Sullivan, Laura N.; Tanaka, David; Fisher, Kimberley; Pittman, Rick; Kumar, Karan R.; Malcolm, William F.; Gustafson, Kathryn E.; Lodge, Andrew J.; Goldberg, Ronald N.; Hornik, Christoph P. (American Journal of Perinatology, 2020)
Objective Prematurity and low birth weight (LBW) are risk factors for increased morbidity and mortality in infants with congenital heart defects (CHDs). We sought to describe survival, inhospital morbidities, and 2-year neurodevelopmental follow-up in LBW infants with CHD.Study Design We included infants with birth weight (BW) <2,500 g diagnosed with CHD (except isolated patent ductus arteriosus) admitted January 2013 to March 2016 to a single level-IV academic neonatal intensive care unit. We reported CHD prevalence by BW and gestational age; selected in-hospital morbidities and mortality by infant BW, CHD type, and surgical intervention; and developmental outcomes by Bayley's scales of infant and toddler development, third edition (BSID-III) scores at age 2 years.Results Among 420 infants with CHD, 28 (7%) underwent cardiac surgery. Median (25th and 75th percentiles) gestational age was 30 (range: 27–33) weeks and BW was 1,258 (range: 870–1,853) g. There were 134 of 420 (32%) extremely LBW (<1,000 g) infants, 82 of 420 (20%) were small for gestational age, and 51 of 420 (12%) multiples. Most common diagnosis: atrial septal defect (260/420, 62%), followed by congenital anomaly of the pulmonary valve (75/420, 18%). Most common surgical procedure: pulmonary artery banding (5/28, 18%), followed by the tetralogy of Fallot corrective repair (4/28, 14%). Survival to discharge was 88% overall and lower among extremely LBW (<1,000 g, 81%) infants and infants undergoing surgery (79%). Comorbidities were common (35%); retinopathy of prematurity and bronchopulmonary dysplasia were most prevalent. BSID-III scores were available on 148 of 176 (84%); any scores <85 were noted in 73 of 148 (49%), with language being most commonly affected.Conclusion Among LBW infants with congenital heart disease, hospital mortality varied by BW and cardiac diagnosis.Key Points
Keywords: low birth weight infants; congenital heart defects; outcomes